Expression of placental growth factor and a disintegrin and metalloprotease with a thrombospondin type motifs 1‐4‐8 during the three trimesters of rat pregnancy at the maternal‐fetal interface - Tatar, Musa; Uslu, Sema; Öner, Jale (Wiley, 2023)
AbstractThe functional roles of the a disintegrin and metalloprotease with a thrombospondin type motifs (ADAMTS) gene family in reproductive physiology, reproductive organs developments and adult reproductive health are still under investigation. The expression of the anti‐angiogenic proteases ADAMTS‐1, ADAMTS‐4 and ADAMTS‐8 in placental angiogenesis at various stages of pregnancy also remains unclear. The purpose of this study was therefore to determine the localization and expression of the ADAMTS‐1, ADAMTS‐4 and ADAMTS‐8 proteins during the three stages of pregnancy in rats. Maternal‐fetal tissue samples were collected on Days 5, 12 and 19 of each trimester, corresponding to the first, second and third trimesters. The expression of placental growth factor (PlGF) and ADAMTS‐1, ADAMTS‐4 and ADAMTS‐8 at the maternal‐fetal interface was examined using immunohistochemistry and western blot at three distinct phases of pregnancy. ADAMTS‐1, ADAMTS‐4 and ADAMTS‐8 were detected in all three trimesters of pregnancy. The relative amount of PIGF increased in the first trimester and decreased significantly in the third trimester (p < 0.05). The expression of ADAMTS‐1 and ADAMTS‐4 was significantly higher in the second (p < 0.05) and third trimesters (p < 0.01) compared to the first trimester. However, no statistically significant change was observed in ADAMTS‐8 expression between trimesters. The ADAMTS exhibiting the highest expression during the first trimester was ADAMTS8. These findings indicate that the expression of ADAMTS‐1, ADAMTS‐4 and ADAMTS‐8 in the three different stages of rat pregnancy may be involved in the modulation of decidualization, morphogenesis and angiogenesis. Periodic changes in ADAMTS expression are thought to be regulated by gonadal steroids.
Keywords: ADAMTS Proteins; Pregnancy; Disintegrins; Placenta; Animals; Female; Rats; Placenta Growth Factor